Extraskeletal Chondrosarcoma of Labium Majus - Arshad S. Khan; Girish D. Bakhshi; Aftab Shaikh; Ashraf A. Khan; Adil A. Khan; Arun Chitale (Case Reports in Pathology)
Extraskeletal myxoid chondrosarcoma (ESMC) is a rare tumor seen more often in men. It is seen to arise from soft tissue of lower extremity or buttocks. We report a case of soft tissue swelling of left labium majus in a 66-year-old female. Patient underwent wide excision with uneventful postoperative course. Histopathology of specimen confirmed it to be ESMC. Patient refused adjuvant therapy. Followup of 1 year has shown her to be disease- and symptom- free. Only two cases arising from vulva have been reported in literature . This is the third case and first from Indian subcontinent. A brief review of clinical features, diagnosis, treatment, and outcome of patients with extraskeletal chondrosarcoma is presented.